#TITLE_ALTERNATIVE# - RAKA ROYNANTA ALDY ( NIM 15010018 ), ALESSANDRO
This paper presents a theoretical and experimental study on active control 20 story steel frame building’s structure excited by earthquake loads using active bracing system. The background of using this active bracing system as a control device is the excessive deformation that occurs in the structure that can cause discomfort for the building user. The control mechanism control is done by using the existing bracing on the building’s structure that actively provide control forces to the structure based on the structure’s responses that measured continuously. This structure was tested with three excitation earthquake loads: El Centro 1940 earthquake, Kobe 1995 earthquake, and Northridge 1994 earthquake. The configurations of bracing was selected based on the smallest structure’s response. On the other hand, for bracing’s type was selected based on the maximum control forces and nominal forces in resisting local buckling of bracing. Analyses is done by observing the effectivity of active bracing system on the steel frame structure excited earthquake loads. On this paper, writer uses two algorithm for calculation the control forces, which is optimal control algorithm and pole placement algorithm. Furthermore, the comparative study between those algorithms will be done in reducing displacement responses in structure